2015
DOI: 10.1111/hpb.12447
|View full text |Cite
|
Sign up to set email alerts
|

Safety and feasibility of an enhanced recovery pathway after a liver resection: prospective cohort study

Abstract: Enhanced recovery after a liver resection appears to be safe, feasible and may reduce severe complications. However, the LOS was significantly influenced by patient age, open surgery and post-operative complications, but not by an ERP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 39 publications
1
41
0
1
Order By: Relevance
“…Despite Dunne (14) reporting similar length of stay, that study was indeed a comparison of early versus late cohort of patients treated with the same protocol and there was reduction in number of patients staying more than 10 days. Dasari et al (15) reported similar findings, however pre-ERAS and post-ERAS cohorts are difficult to compare since author unit already practiced some fast-track elements in their perioperative care before introduction of standardized protocol. Overall morbidity seems not to be affected by ERAS management, with some studies demonstrating decrease in medical and low-grade Clavien grade I-II complications.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Despite Dunne (14) reporting similar length of stay, that study was indeed a comparison of early versus late cohort of patients treated with the same protocol and there was reduction in number of patients staying more than 10 days. Dasari et al (15) reported similar findings, however pre-ERAS and post-ERAS cohorts are difficult to compare since author unit already practiced some fast-track elements in their perioperative care before introduction of standardized protocol. Overall morbidity seems not to be affected by ERAS management, with some studies demonstrating decrease in medical and low-grade Clavien grade I-II complications.…”
Section: Discussionmentioning
confidence: 85%
“…Overall morbidity seems not to be affected by ERAS management, with some studies demonstrating decrease in medical and low-grade Clavien grade I-II complications. The only study reporting decrease in major complications (grade III-V) is by Dasari et al (15), which appears to be mostly secondary to higher rate of intra-abdominal collections. There are no details given on a nature of intra-abdominal collections but in reviewing both pre-ERAS and ERAS cohorts, there is increased number of extended resections, open hepatectomy, hepatocellular (10) reported increase in readmission rates with parallel decrease of length of stay under ERAS protocol below 4 days while overall complication rate was unaffected.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Six studies were RCTs, 22,25,28,29,32,35 16 were case-control studies 2, 18, 21, 23, 24, 27, 31, 33, 36-42 and five prospective studies. 19,20,26,30,34 Eleven studies included both open and laparoscopic surgery in the study, 19-21, 23, 24, 27, 33, 35, 37, 39, 40 ten studies included only open liver surgery patients, 2, 18, 25, 26, 30-32, 34, 41, 42 five studies included only laparoscopic surgery patients, 22,28,29,36,38 whilst one study performed a separate analysis for laparoscopic surgery and open surgery. 21 A detailed characteristic of included studies is shown in Table 1.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Intermittent inflow vascular control was obtained based on the extent of resection and surgeon preference. Abdominal drains were used after most resections, but were removed according to an enhanced recovery protocol (in use in the department since 2014). Anatomical remnant liver volumes were measured selectively in patients requiring extended hepatectomy.…”
Section: Methodsmentioning
confidence: 83%